Extension of a Function from the Exterior of an Interval to a Positive-Definite Function on the Entire Axis and an Approximation Characteristic of the Class $W_M^{r, β}$ - Zastavnyi, V. P. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We establish sufficient conditions for the extension of a function defined on $[a, +∞)$, where $a > 0$, to a positive-definite function on the entire axis.